Purchasing and Marketing of Social and Environmental Sustainability for High-Tech Medical Equipment - Lindgreen, Adam (Journal of business ethics, 2009)
As the functional capabilities of high-tech medical products converge, supplying organizations seek new opportunities to differentiate their offerings. Embracing product sustainability-related differentiators provides just such an opportunity. This study examines the challenge organizations face when attempting to understand how customers perceive environmental and social dimensions of sustainability by exploring and defining both dimensions on the basis of a review of extant literature and focus group research with a leading supplier of magnetic resonance imaging (MRI) scanning equipment. The study encompasses seven hospitals and one private imaging center in the Netherlands and identifies five social aspects that cover 11 indicators. The authors conduct 22 customer perception interviews with key decision-making stakeholders involved in purchasing MRI scanning equipment. Respondents find environmental and social sustainability dimensions personally relevant but professionally secondary to cost, performance, and ability to use the equipment in their organizations’ physical infrastructure. Finally, incorporating a product’s environmental and social credentials within the marketing of MRI scanning equipment enhances the perception of the product offering in decision-making stakeholders’ minds and provides a means of differentiation.